Pioglitazone Ameliorates Neuron Loss in the Cortex after Aluminum-Treatment in Rats. (8th June 2015) - Rafati, Ali; Yazdani, Hajar; Noorafshan, Ali
Abstract : The objective was evaluation of the effects of pioglitazone on medial prefrontal cortex (mPFC) of the rats exposed to aluminum (Al). Al induces structural changes in several brain regions, including mPFC. Pioglitazone is an agonist of peroxisomal proliferator activated receptor gamma. Male rats were randomly assigned to control, Al-treated (10 mg/kg/day), and Al + PIO-treated groups (Al+ 40 mg/kg/day). After 56 days, the right mPFCs were removed. Then, the volume of mPFC and its subdivisions, volume of vessels, and total number of neurons and glia were estimated using stereological methods. The results showed 13–38% decrease in the volume of the mPFC and its subdivisions, mainly in the infralimbic region (P < 0.02 ). Besides, the volume of the vessels reduced by 47% after Al-treatment (P < 0.02 ). The total number of the neurons and glial cells was also reduced (40% and 25%, resp.) in the Al-exposed rats in comparison to the control ones (P < 0.02 ). Treatment of the animals with Al + PIO ameliorated the neuron loss and no improvement was seen in other parameters (P < 0.02 ). It can be concluded that treatment of the rats with PIO could ameliorate the neuron loss in the mPFC of the Al-treated animals.